Aboveground biomass in tropical dry forest at Rote Ndao Regency, East Nusa Tenggara Province, Indonesia - Ahmad Almulqu, Aah; Boonyanuphap, Jaruntorn (Asian Health, Science and Technology Reports, 2018)
The study of biomass storage in trees in the tropical dry forest at Rote Ndao Regency, East Nusa Tenggara, Indonesia is conducted. The biomass of standing trees is estimated by non destructive method. The tree height and diameter is taken into consideration for the measurement of biomass and carbon content. The height of tree is measured by using a theoretical model and concept is used for actual measurement of 7 different tree species (Schleichera oleosa, Dryobalanops aromatic, Mangifera indica, Cordirchotoma torsi, Tamarindus indica, Ficus benjamina and Vitex parviflora) having diameter at breast height (DBH) ≥ 20 cm. The total of carbon storage has been determined and compared with allometric equation. At the time of estimation of organic carbon storage by allometric equation, the study revealed that allometric equation based on two approach, namely only use DBH and use DBH. Based on results of research, show that the total of carbon stock, respectively, were 8,600.22 ton/ha ton/ha in Schleichera oleosa, followed by Dryobalanops aromatica (3491.438 ton/ha), Mangifera indica (2997.458 ton/ha), Vitex parviflora (2147.406 ton/ha), Tamarindus indica (545.116 ton/ha), Ficus benjamina (387.292 ton/ha) and Cordirchotoma torsi (288.176 ton/ha).